The pottery assemblage - Ballin-Smith, Beverley (Scottish Archaeological Internet Reports, 2011)
A total of 195 sherds representing a minimum of 16 vessels from the early Neolithic to the Bronze Age was recovered. The assemblage included early Neolithic bowls, grooved ware and Beaker sherds.